Booms, busts and parochialism: Western Australia's implacable political geography. (August 2016) - Beeson, Mark
Western Australia (WA) has recently assumed an unaccustomed centrality in the minds of Australian policymakers. The recent resource boom briefly propelled WA to the forefront of national economic affairs. While this proved a relatively short-lived prominence, the emergence of WA at the centre of a putative 'Indo-Pacific' region promises to give it a more enduring strategic significance. This paper details how geopolitical and geoeconomic forces have shaped WA's developmental history, and why they are likely to do so in the future as well.